2020
DOI: 10.1111/bjd.19485
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins associated with development of metastasis from cutaneous squamous cell carcinomas (cSCCs) via proteomic analysis of primary cSCCs*

Abstract: Summary Background Cutaneous squamous cell carcinoma (cSCC) is one of the most common cancers capable of metastasizing. Proteomic analysis of cSCCs can provide insight into the biological processes responsible for metastasis, as well as future therapeutic targets and prognostic biomarkers. Objectives To identify proteins associated with development of metastasis in cSCC. Methods A proteomic‐based approach was employed on 105 completely excised, primary cSCCs, comprising 52 that had metastasized (P‐M) and 53 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
(87 reference statements)
1
22
0
Order By: Relevance
“…It is recognised that the immune system plays an important role in tumorigenesis and cancer metastases, including in skin cancer [38,39]. Indeed, it has been shown that immunosuppressed individuals have an increased risk of developing melanoma [40], and that immunosuppressed individuals are at much greater risk of developing metastasis than immunocompetent individuals [41].…”
Section: Discussionmentioning
confidence: 99%
“…It is recognised that the immune system plays an important role in tumorigenesis and cancer metastases, including in skin cancer [38,39]. Indeed, it has been shown that immunosuppressed individuals have an increased risk of developing melanoma [40], and that immunosuppressed individuals are at much greater risk of developing metastasis than immunocompetent individuals [41].…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of 48 RNA samples, despite the small sample size, several microRNAs were found to show differential expression between primary tumors which metastasized and those that did not [ 28 ]. Finally, in a proteomic-based study including 105 CSCC samples, half of which metastasized within 5 years from surgery, increased expression of two proteins, ANXA5 and DDOST, was significantly associated with development of metastasis, highlighting the potential role of proteomic analysis into risk stratification of patients with CSCC [ 29 ]. However, as of today, the impact of molecular and epigenetic characterization on prognosis and targeted treatments is not entirely clear, and it should not be routinely performed in everyday clinical practice, outside of translational studies ( expert recommendation 4 ).…”
Section: Pathogenesis and Molecular Characteristicsmentioning
confidence: 99%
“…It may be surprising to many readers that an analysis of the proteins expressed in primary cSCC that are associated with metastasis (or indeed clinical outcomes) has not been reported previously. So, in this regard, the study by Shapanis et al 5 . is particularly important and timely.…”
mentioning
confidence: 94%
“…It may be surprising to many readers that an analysis of the proteins expressed in primary cSCC that are associated with metastasis (or indeed clinical outcomes) has not been reported previously. So, in this regard, the study by Shapanis et al 5 is particularly important and timely. Moreover, this study is innovative as it deployed a combination of proteomics, machine learning and mathematical modelling to identify key prognostic indicators in cSCC.…”
mentioning
confidence: 94%
See 1 more Smart Citation